Optimal adaptive control for quantum metrology with time-dependent Hamiltonians - Shengshi Pang (Nature Portfolio, 2017)
Quantum metrology investigates the improvement given to precision measurements by exploiting quantum mechanics, but it has been mostly limited to systems with static Hamiltonians. Here the authors study it in the general case of time-varying Hamiltonians, showing that optimizing the quantum Fisher information via quantum control provides an advantage.